Current status and influencing factors of job crafting ability in operating room senior nurses: a cross-sectional study - Lian, Qiwen; Huang, Weizhao; Guo, Tingting; Li, Binfei; Luo, Xiaoping (Frontiers in Psychology, 2025)
BackgroundSenior nurses are pivotal to healthcare quality but face heightened burnout and career stagnation, especially in high-stakes environments like the operating room (OR). Job crafting, a proactive behavior where employees reshape their work, is a potential strategy to enhance their resilience and engagement. However, evidence on job crafting and its drivers among OR senior nurses remains limited.AimsTo investigate the job crafting ability of OR senior nurses and its influencing factors within a specific regional context, providing a basis for targeted interventions.DesignA cross-sectional study.MethodsIn February–May 2025, 210 OR senior nurses from four hospitals in Zhongshan, China (including 2 tertiary hospitals, 1 secondary hospital, and 1 primary care institution) were selected via convenience sampling. Data were collected using general information, job crafting, organizational support, and professional identity scales. Analyses included descriptive statistics, t-test, ANOVA, Spearman correlation, and multiple linear regression.ResultsThe job crafting score (21 items) averaged 68.04 ± 22.876, indicating a lower-middle level. Multiple linear regression revealed that organizational support (β = 0.679, P < 0.001), professional identity (β = 0.273, P < 0.001), hospital grade, and employment type were significant predictors, collectively explaining 75.7% of the variance in job crafting scores.ConclusionAmong OR senior nurses in the surveyed hospitals of Zhongshan, job crafting was at a lower-middle level and significantly influenced by organizational support, professional identity, hospital grade, and employment type. The findings, primarily reflective of a female-dominated sample within this specific context, suggest that nurse managers should develop strategies targeting these factors to enhance job crafting. However, the generalizability of these conclusions to other regions or different gender compositions requires further investigation.